Impact of Calcium and Nitrogen Addition on Bioethanol Production by S. cerevisiae Fermentation from Date By-Products: Physicochemical Characterization and Technical Design - Fahad M. Alminderej; Zeineb Hamden; Yassine El-Ghoul; Bechir Hammami; Sayed M. Saleh; Hatem Majdoub (Fermentation, 2022)
Given crude oil prices and their environmental impacts, the use of sustainable renewable alternative energies such as biofuels is rapidly progressing in numerous countries. Among biofuels, bioethanol is a renewable and clean fuel that can be obtained from the fermentation of several raw agricultural materials, including date fruit. However, the low product yield, mainly due to the low-grade nutrient content, limits its use as a promising alternative biofuel. This current study investigated bioethanol production from date by-products in Saudi Arabia and examined the impact of calcium and nitrogen sources added at different concentrations (0 to 1 g/L) on the productivity and ethanol concentration using Saccharomyces cerevisiae. Yeast extracts and ammonium chloride (NH4Cl) were tested as nitrogen sources for bioethanol fermentation from date juice. Calcium chloride (CaCl2) and calcium carbonate (CaCO3) were evaluated as calcium sources for the same purpose mentioned above. The results showed that both calcium and nitrogen sources improved ethanol production efficiencies. The addition of calcium sources such as CaCl2 at 0.4 g/L resulted in maximum ethanol concentration (41.5 ± 0.85 g/L) and the highest productivity of 0.511 g/L/h. Thus, an increase of 31.3% compared to the control sample was acquired. Ammonium chloride was found to be the best nitrogen supplement among them. Indeed, supplementing the fermentation medium with 1 g/L NH4Cl gave an optimal ethanol concentration and productivity, reaching more than 65 g/L and 0.83 g/L/h, respectively. This is an increase of 106.6%. The functional group of ethanol (C2H5OH) for all the elaborated samples was confirmed by Fourier-transform infrared spectroscopy (FTIR) and NMR analyses. Moreover, the results confirmed the high quality and purity of the bioethanol products. Thus, the “Khodhari” date variety of low market value is a privileged substrate for industrial bioethanol production. For this reason, a proposed flow diagram of a designed plant for bioethanol industrialization is provided and detailed.